GL YCOHEM OG LOB IN AND INCIDENCE OF CORONARY HEART DISEASE - Jamil, Nargis; Shafiq, Mohammad; Tasneem, Kausar; Lutfullah, Ghosia; Rehman, Jamil ur (Journal of Ayub Medical College Abbottabad, 2000)
Background: Presence of glucose on Hb1-c is established and represents a post translational glycosylation by a slow non-enzymatic process occurring during the 120 days’ life span of RBCs. It is an indicator of long term glycemic control. Glycohemoglobin is directly related to blood glucose level. Methods: 50 randomly selected diabetic patients were included and divided into two groups B and C of 25 subjects each. The subjects of group C were the diabetics who were confirmed cases of CHD. while group B were the diabetics without any complications. Group A consisted of healthy controls (n=25). Glycohemoglobin was determined by column chromatography while blood glucose was estimated by enzymatic method. Results: Blood glucose was increased in both the patient groups (p<0.001). Comparison of HbA| revealed a highly significant rise (p<0.001) in both the groups against normal control subjects of group A. Correlation of Hb1-c with glucose in all the three groups was directly positive (r=+0.4). Conclusions: The results of the present study suggest an association between HbA1-c hyperglycemia and the incidence of CHD in diabetics.